Molecular characterization of α-lactalbumin (LALBA) protein in Indian buffalo (Bubalus bubalis) - mehra, vinay kumar; Malakar, Dhruba; Kumar, Satish (Indian Journal of Dairy Science, 2022)
The full open reading frame (ORF) of the buffalo beta-lactoglobulin (Bu_LALBA) gene was characterized. Results showed that Bu_LALBA ORF consisted of 429 bp long (142 aa residues) with three nucleotide variations at 111bp, 147 bp, and 291 bp but no change in amino acid sequence. The MSA showed that the Bu_LALBA was more different from the pig and human LALBA sequences. The phylogenetic tree showed that the cow, yak, and buffalo formed one cluster, while the buffalo was more closer (94%) to domestic yak (Bos grunniens). Results of ExPASy analysis showed that the Bu_LALBA protein was acidic (pI, 4.81), thermo-tolerant, and hydrophilic. However, the presence of random coil (33.80%) and Î±-helix (41.5%) in Bu_LALBA protein suggest that the protein was flexible and thermostable. Thirty liner motifs were identified, indicating that the Bu_LALBA act as regulatory protein. The tertiary structure of Bu_LALBA predicted by I-TASSER showed a more stabilized nature of LALBA protein. Further, the Ramachandran plot validated the 3-D structure of Bu_LALBA, which was of decent quality. The presence of four ligand-binding sites in Bu_LALBA (calcium ion, glycine, N-acetyl-L-glutamate, and N-acetylglucosamine) proposed that the LALBA binds to several fatty acids and ions. The presence of four serine, four threonine, two tyrosine residues, and six methylated lysine and five acetyl-lysine sites in Bu_LALBA indicated that the protein was involved in post-translational modification processes. IEDB analysis showed the presence of five and one epitope sites in Bu_LALBA protein for B-cell and T-cell, respectively, which suggest that this protein has certain immunological roles.Â